HUBUNGAN EDUKASI CUCI TANGAN TERHADAP PENGETAHUAN, SIKAP, KEMAMPUAN KELUARGA DI RUMAH SAKIT X PALEMBANG - Satiti, Angela; Frisca, Sanny; Nurjanah, Vausta (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Families of patients who are in the hospital have an important role in preventing nosocomial infections by increasing the knowledge and attitude of hand washing in hospitals by increasing their knowledge and attitude of eating will also increase the ability to wash hands. However, the implementation of hand washing in the patient's family has not run optimally due to various reasons. The patient's family said that they did not know how to wash their hands properly and some said that they did not wash their hands because the patient's disease was not contagious.this study aims to determine the relationship of hand washing education to knowledge, attitudes and abilities of family members in the X Palembang Hospital.Method: This research is a quantitative type of research using quasi experimental with a Non Equavalent Control Group plan and a sample of 112 respondents used purposive sampling technique. The data analysis technique used is the Fisher Exact.The results of this study indicate that there is a relationship between hand washing education to the knowledge, attitudes, ability, of the families of patients at X Palembang Hospital (p value= 0.001<0.005), For this reason, the role of nurses as educators is needed, providing counseling to families of patients treated at Hospital so that nosocomial infections can be prevented.Keywords: Knowledge, Attitude, Ability, Hand Washing